4D printing using anisotropic thermal deformation of 3D-printed thermoplastic parts. (March 2020) - Goo, Bona; Hong, Chae-Hui; Park, Keun
Abstract: Four-dimensional (4D) printing is an advanced application of 3D printing with the additional shapes changes over time. For appropriate shape changes, 4D printing has been developed using shape memory materials or multi-material structures with different deformation behaviors in response to an external stimulus. In this study, an efficient 4D printing method was developed using a material extrusion (ME) type 3D printer and a single thermoplastic polymer without a shape memory function. To impose different deformation behaviors in a single thermoplastic material, the printing paths were programmed intentionally, and the resulting anisotropy was used to generate a unique thermal deformation in response to a thermal stimulus. The anisotropic thermal deformations of the longitudinally and transversely printed parts were investigated by analyzing the directional size changes of homogeneously laminated bars. This anisotropy was then used to enable 4D printing by applying heterogeneous lamination in which the transverse and longitudinal printing paths were used consecutively. This heterogeneous lamination showed bending deformation after heat treatment, and the effect of lamination strategy on the order of bending was investigated experimentally. The proposed 4D printing method was further applied to induce localized bending deformation by laminating isotropic and anisotropic regions selectively, which enabled a self-assembly function. Graphical abstract: Unlabelled Image Highlights: An efficient 4D printing method was developed using a single thermoplastic polymer without a shape memory function. To enable shape transformation, the printing paths were programmed to impose bidirectional anisotropy intentionally. The difference in thermal deformation of transversely and longitudinally printed layers were caused bending deformation. The selective lamination of isotropic and anisotropic regions enabled a localized bending for a self-assembly function.